Penyebab Anemia Pada Remaja Puteri - Yudi Alfian; Mira Octaviani Malik; Maya Arfania (Peneliti.net, 2023)
Anemia is a condition characterized by reduced hemoglobin in the body. Hemoglobin is a metalloprotein, namely a protein containing iron in red blood cells that functions as a carrier of oxygen from the lungs throughout the body. Iron deficiency anemia is anemia caused by a lack of iron which is used for the synthesis of hemoglobin (Hb). Anemia is the second highest cause of disability in the world. This is because anemia can cause various complications, including decreased endurance, cognitive impairment, stunted growth, decreased activity, and changes in behavior. The data used in writing this article review was collected using the literature study method. Literature searches were carried out using online-based literature search instruments, such as from 3 sources namely, Google sholar, pubmed, and science direct journals taken in this study consisted of 8 international journals and 2 national journals from the year range (2012-2022).